Synthesis of New 5-Oxazolones: Their Ring Opening Reactions to Obtain New Benzamide Derivatives - Gunkara, Omer Tahir; Guleli, Muge; Cevikkalp, Senem Akkus; Kaya, Kerem; Ocal, Nuket (BENTHAM SCIENCE PUBL LTD, 2017)
New 5-oxazolones have been synthesized via N-protected amino acids which were prepared from various aryl acyl halides and L-amino acids, with DCC. Then, we studied the ring opening reactions of 5-oxazolones with nucleophilic attack by primary aryl amines to obtain new racemic benzamide derivatives. All new synthesized compounds have been characterized by FTIR, H-1, C-13 NMR, GC/MS, LC/MS and Qtof analyses. X-Ray results of N-(1-((4-chlorophenyl) amino)-3-methyl-1-oxopentan-2-yl)-3-(trifluoromethyl) benzamide clearly showed absolute stereostructure.
Keywords: Benzamides; biological activity; heterocycles; nucleophilic attack; 5-oxazolone; ring opening reactions; ACID; INHIBITORS; RESOLUTION; MECHANISM; Chemistry